2015
DOI: 10.1097/hjh.0000000000000403
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic power of lower pulse pressure on long-term all-cause mortality in octogenarians with acute coronary syndrome

Abstract: This study reveals a U-shaped association of mortality rate with PP in the octogenarians with ACS and demonstrates that PP equal to or less than 50  mmHg has an independent prognostic power in long-term all-cause mortality in the octogenarians with ACS as well as the subgroup with hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Li et al [7] indicated that PP lower than 50 mm and higher than 70 mmHg increased the mortality rates significantly in patients with ACS who were over 80 years old. Patients with PP between these two values had the best prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Li et al [7] indicated that PP lower than 50 mm and higher than 70 mmHg increased the mortality rates significantly in patients with ACS who were over 80 years old. Patients with PP between these two values had the best prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, no upper or lower limit was determined for blood pressure values. Patients with blood pressure values between 170/100 mmHg and 130/60 mmHg were considered similarly since their PP was 70 mmHg [7] . In our study, A-STEMI patients with normal SBP and DBP were followed according to the recommendations of current guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations